Implementation of LFP Batteries for Energy Storage at Small hydro power station - Huang Tianshuo (E3S Web of Conferences)
With the application of energy storge system (ESS) in large powerplants are become increasingly mature, there’s an absent of small hydropower stations. Small hydropower stations, though considered as a clean energy, are facing government regulations about restrict it outflows due to environmental protection. To help these small hydropower stations survive, ESS is needed. In this article, the battery that was used in large powerplants ESS is explored to figure out how to adopt the technology into way smaller powerplant by analysing technological, economic and construction factors. The results suggest that ESS using LFP battery can significantly improve energy consistency under outflow restriction. However, on the economic aspect, with the rapid decrease in the battery prices and different policy in different regions, the outcomes can be diverse, but the overall dropping battery prices and increasing demand of renewable energy led to a promising future. This article has illuminated the direction for the development of technology.